Cognitive activity and creativity of seniors connection with the levels of reflexivity - Сачок, Ксенія Миколаївна; Заїка, Євген Валентинович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
There were represented the results of experemental studies of the cognitive activity and creativity among high school students which correlate with different levels of reflexivity. The results showed that school students with low reflexivity have low rates in cognitive activity and creativity, those with average level of reflexivity have the average level of cognitive activity, but with high level of creativity - high rates of the uniqueness index, students with high reflexivity have the high level of cognitive activity and the average level of creativity .Also we proposed recommendations for trainings among school students.